Biscuit With Substitution Of Red Bean Flour and Taro Flour - Lilis Nurlinda Sari; Sitti Sahariah Rowa; fatmawaty suaib (Jurusan Gizi Poltekkes Kemenkes Makassar, 2019)
Indonesia faces two nutritional problems, namely malnutrition and over nutrition. Malnutrition is caused by lack of food supply, food distribution, poverty, ignorance, wrong eating habits and health. One of the ways to overcome malnutrition among the community is by using red beans and taro into flour in the form of biscuit snacks by considering the nutrients, their benefits and their acceptability. This study aims to determine the acceptability and analysis of macro nutrient of biscuit content by substituting red bean flour and taro flour. The research design was experimental with a one shot goup design. Acceptance was assessed based on a hedonic test of 30 panelists. The results of the best acceptability were analyzed for their macro nutritional value, protein testing at the laboratory using method micro Kjedal method, fat using the soxhlet and carbohydrate method using method luff schroll method. Then presented in the form of tables and narratives. The results showed that the panelists received the highest power on biscuits with the substitution of red bean flour and taro flour which was Xconcentration1. Panelists were very fond of 100% color aspects, 96.7% aroma, 100% texture and 100% flavor. The nutritional value of biscuits with a concentration of X1 is 5.020% protein, 32.33% fat and 19.81% carbohydrate. It is suggested in making biscuits by substituting red bean flour and taro flour to add more red bean flour in the hope that protein nutritional value can increase. It is better to test other nutrients in biscuits.